Effectiveness of scapular mobilization in patients with primary adhesive capsulitis: A systematic review and meta-analysis - Olguín Huerta, Cristian Rodrigo.; Araya Quintanilla, Felipe.; Moncada Ramírez, Victoria.; Estrella Flores, Evelin.; Cuyul Vásquez, Iván.; Gutiérrez Espinoza, Héctor J. (Lippincott Williams and Wilkins, 2023)
Background: The aim of this study was to determine the effectiveness of scapular mobilization on range of motion, shoulder disability, and pain intensity in patients with primary adhesive capsulitis (AC). Methods: An electronic search was performed in the MEDLINE, EMBASE, SCOPUS, CENTRAL, LILACS, CINAHL, SPORTDiscus, and Web of Science databases up to March 2023. The eligibility criteria for selected studies included randomized clinical trials that included scapular mobilization with or without other therapeutic interventions for range of motion, shoulder disability, and pain intensity in patients older than 18 years with primary AC. Two authors independently performed the search, study selection, and data extraction, and assessed the risk of bias using the Cochrane Risk of Bias 2 tool. Results: Six randomized clinical trials met the eligibility criteria. For scapular mobilization versus other therapeutic interventions, there was no significant difference in the effect sizes between groups: the standard mean difference was -0.16 (95% confidence interval [CI] = -0.87 to 0.56; P =.66) for external rotation, -1.01 (95% CI = -2.33 to 0.31; P =.13) for flexion, -0.29 (95% CI = -1.17 to 0.60; P =.52) for shoulder disability, and 0.65 (95% CI = -0.42 to 1.72; P =.23) for pain intensity. Conclusions: Scapular mobilization with or without other therapeutic interventions does not provide a significant clinical benefit regarding active shoulder range of motion, disability, or pain intensity in patients with primary AC, compared with other manual therapy techniques or other treatments; the quality of evidence was very low to moderate according to the grading of recommendation, assessment, development and evaluation approach.
Keywords: Adhesive capsulitis; Frozen shoulder; Musculoskeletal manipulations; Range of motion; Scapular mobilization; Meta-análisis